Principles of data-base management - Martin, James (Engle Cliffs, NJ : Prentice-Hall, 1976)
This book covers such topic as logical and physical data structure, data security, accuracy and privacy and dialogue with a database system terminal.
includes index
kjo 15/01/2019
Loans
Keywords: Database management